2008
DOI: 10.1038/clpt.2008.101
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Algorithms to Predict Warfarin Maintenance Dose in Caucasians and African Americans

Abstract: Objectives-The objective of this study was to determine whether clinical, environmental, and genetic factors can be used to develop dosing algorithms for Caucasians and African Americans that perform better than giving empirical 5 mg/day. Methods-From April 2002 through December 2005, 259 warfarin initiators were prospectively followed until they reached maintenance dose.Results-The Caucasian algorithm included 11 variables (R 2 =0.43). This model (51% within 1 mg) performed better compared with 5 mg/day (29% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
95
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 37 publications
12
95
1
Order By: Relevance
“…In Croatian population, the prevalence of variant CYP2C9*2 and *3 alleles is estimated to be 35% (Božina), which is similar to some other data published for Caucasians (41,43).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In Croatian population, the prevalence of variant CYP2C9*2 and *3 alleles is estimated to be 35% (Božina), which is similar to some other data published for Caucasians (41,43).…”
Section: Discussionsupporting
confidence: 74%
“…Studies of inter-ethnic differences in sensitivity to warfarin confirmed that the VKORC1 polymorphism had significantly greater influence on the variability of dose in Asians and Caucasians than in Afro-Americans as the result of race-specific differences in the frequency of VKORC1 polymorphisms (40)(41)(42)(43). A studies conducted confirmed that this is due to differences in MAFs (minor allele frequency) across racial groups.…”
Section: Discussionsupporting
confidence: 48%
“…9,16,22 Furthermore, three genome-wide association studies failed to find any additional genetic loci other than those herein studied (CYP2C9, CYP4F2 and VKORC1) with regard to influence on warfarin dose requirement. 23,24 In conclusion, in this first report on the impact of genetic, clinical and demographic factors involved in warfarin dose requirement in the Omani patients, a significant percentage of variability still (around 37%) awaits explanation.…”
Section: Vkorc1_9041 N (%)mentioning
confidence: 66%
“…Limdi et al, 1 in a recent study demonstrated that VKORC1 3673G4A polymorphism was predictive of warfarin dose across three racial groups, namely Asians, Blacks and Whites, but its contribution varies between 11 and 32% amongst Caucasians, 30% in Asians and 4-10% in African Americans, reflecting its relative frequency in each population. 9,10,15,16 28 (20) 17 (24) n.s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation